The relationship between total quality management practices and academic performance of primary school and teaching innovation as mediator in Abu Dhabi - Alhosani, Mohamed Salem Ahmed Ibrahim (Tanjong Malim, 2023)
The relationship between total quality management practices and academic performance of primary school and teaching innovation as mediator in Abu Dhabi by Alhosani, Mohamed Salem Ahmed Ibrahim